Protective Ability of Biogenic Antimicrobial Peptide Microcin J25 Against Enterotoxigenic Escherichia Coli-Induced Intestinal Epithelial Dysfunction and Inflammatory Responses IPEC-J2 Cells - Yu, Haitao; Ding, Xiuliang; Shang, Lijun; Zeng, Xiangfang; Liu, Hongbin; Li, Ning; Huang, Shuo; Wang, Yuming; Wang, Gang; Cai, Shuang; Chen, Meixia; Levesque, Crystal L.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Foods or feedstuffs contaminated by enterotoxigenic Escherichia coli (ETEC) cause severe health problems in human infants and young animals. With the emergence of public health concerns and rapid spread of drug-resistance of bacteria, there is extraordinary interest in antimicrobial peptides as potential candidates in treating pathogen infections. Nature Microcin J25 (MccJ25), a member of the class of lasso peptides isolated from a fecal strain of E. coli, has been reported to exhibit strong antimicrobial activity against gram-negative bacteria. Herein, the study was to evaluate the efficacy of biogenic MccJ25 in the prevention of ETEC K88 infection in IPEC-J2 cells. In vitro antimicrobial activity against ETEC K88 and cytotoxicity of biogenic MccJ25 were determined first. To further understand how biogenic MccJ25 mediates its impact, ETEC K88 adhesion in cells, membrane permeability [as indicated by reduced release of lactate dehydrogenase (LDH)], transepithelial electrical resistance (TEER), barrier function and proinflammatory cytokines levels were determined in IPEC-J2 cells after treatment with biogenic MccJ25 and challenge with ETEC K88. Biogenic MccJ25 had a minimum inhibitory concentration of 0.25 μg/mL against ETEC K88, decreased ETEC K88 adhesion in cells and did not cause cytotoxicity towards cells. Furthermore, biogenic MccJ25 protects against ETEC-induced barrier dysfunction by increasing the TEER, decreasing the LDH and promoting tight junction proteins by promoting the assembly of occludin and claudin-1 in the tight junction complex. Biogenic MccJ25 was further found to relieve inflammation responses through modulation of interleukine-6, IL-8 and tumor necrosis factor-α levels via inhibition of mitogen-activated protein kinase and nuclear factor κB activation. In summary, biogenic MccJ25 can protects against ETEC K88-induced intestinal damage and inflammatory response, suggesting the potential use of biogenic MccJ25 as a novel prophylactic agent to reduce pathogen infection in animals, food or humans.